σ meson exchange effect on non-mesonic hypernuclear weak decay observables - Barbero, César Alberto (2006)
We analyze the influence of σ meson exchange on the main non-mesonic hypernuclear weak decay observables: Total rate ΓNM, neutron-to-proton branching ratio Γn/p, and proton asymmetry parameter aΛ. The σ meson exchange is added to the standard strangeness-changing weak ΛN → NN transition potential, which includes the exchange of the complete pseudoscalar and vector mesons octet (π, η, K, ρ, ω, K*). Using a shell model formalism, the σ meson weak coupling constants are adjusted to reproduce the recent ΓNM and Γn/p experimental data for ⁵ΛHe. Numerical results for the remaining observables of ⁵ΛHe and all the observables of ¹²ΛC decays are presented. They clearly show that the addition of the σ meson improves the agreement with the data. However, its effect it is not enough to reproduce well the aΛ values, which means that other improvements of the model must be explored to explain the puzzle posed by the experiments.